Behavioural Analysis of Stakeholders towards Socio-Economic Change: The Energy Transition Journey in the Area of Gela - MORSELLI, Alessandro; ARSINI, Valentina; Di VINCENZO, Alessandra (Theoretical and Practical Research in Economic Fields; Vol 12 No 2 (2021): TPREF, Volume XII, Issue 2(24), Winter 2021, 2021)
This work is divided into three parts. Part One describes the reference literature and in particular the Rogers curve, which is helpful to understand the stage of adoption of innovations in which the population of the Gela area is. According to this theory, the process of acquisition of new technologies follows a customary pattern that may be useful to describe in detail the current attitude of the population towards the conversion in place and to assess or change the implementation of any interventions. Part Two involves the preparation and distribution of a questionnaire of 20 closed-answer questions to investigate: personal data, lifestyle to protect the environment, daily habits on recycling, waste and sustainable mobility, interests in circular economy and potential inclination of the area for its economic development. Part Three concerns the analysis of the answers to the questionnaire, in the light of the Rogers curve, to understand whether or not the data confirm the existence of innovators, in order to understand the impact on the success of the conversion in place and suggest possible correction strategies.